D Determinants Of Medication Adherence Among Outpatients With Schizophrenia: The Role Of Health Belief Model Constructs And Family Support - Dian Utama Pratiwi Putri; Takfha Nur Asyifa; Bambang Setiaji; Dewi Rahayu (PT.Mantaya Idea Batara, 2025)
Introduction: Medication adherence is essential for preventing relapse and enhancing the quality of life in individuals with schizophrenia. Despite its importance, consistent adherence remains a significant challenge in outpatient care. The Health Belief Model (HBM) offers a framework for understanding patients’ perceptions of treatment, and family support is critical for sustaining long-term adherence. This study investigated the determinants of medication adherence among schizophrenia outpatients by assessing the influence of HBM constructs and family support in Tangerang Regency, Indonesia. A quantitative analytic cross-sectional design was employed, involving schizophrenia outpatients at three public health centers in Tangerang Regency. Data collection utilized structured questionnaires and interviews to assess medication adherence, HBM constructs, and family support. Statistical analyses included univariate, bivariate, and multivariate approaches. Results indicated that most patients (56%) exhibited moderate medication adherence, with lower (33%) and higher (17%) adherence rates observed in smaller proportions. Significant associations were found between HBM factors and medication adherence, particularly regarding perceived benefits and beliefs about treatment effectiveness. Family support, especially emotional and practical assistance, was also significantly related to adherence. Health belief variables wereidentified as the most influential determinants, followed by family support. Overall, medication adherence among schizophrenia outpatients is primarily influenced by health beliefs and family support systems.